Description of Work Engagement in Primary School Honorary Teachers - Rifda Alda Ufaira; Aulia Nur Imanda; Lalu Reza Gunawan; Soeprapto Soeprapto; Wiwin Hendriani (Psikoislamedia : Jurnal Psikologi, 2020)
The purpose of this study is to figure out of work engagement on temporary teacher. The method used in this study is qualitative with case study approach. This study conduct in Elementary School Gunung Maddah IV Sampang-Madura, East Java Province. The participants were choosen after former interview to the Headmaster to gain initial description about the temporary teacher’s condition in his school. Finally was choosen 2 from 6 temporary teachers as participants in this study. The narratives of two teacher were used to describe work engagement on temporary teacher. The participants narrated the vigor, dedication, and absorption as the key elements in conduct their work engagement.